2015
DOI: 10.1111/cid.12360
|View full text |Cite
|
Sign up to set email alerts
|

Follow‐Up of the Sinus Membrane Elevation Technique for Maxillary Sinus Implants without the Use of Graft Material

Abstract: The present study illustrates the long-term reliability of the technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…Our results regarding new bone formation are in line with several authors showing that the mere elevation of the maxillary sinus membrane at the time of implant insertion results in bone formation …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results regarding new bone formation are in line with several authors showing that the mere elevation of the maxillary sinus membrane at the time of implant insertion results in bone formation …”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the implant survival was 95.9% after 8 years. These results are comparable to a long‐term follow‐up study by Riben and Thor . They reported on 94.3% implant survival after 4.6 years.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“… reported that 96 maxillary sinus membrane‐elevation procedures and the simultaneous placement of 239 oxidized implants, without bone grafts or bone substitutes, resulted in predictable bone formation with a high implant‐survival rate of 98.7% during a follow‐up period of 1–6 years after functional loading. Riben & Thor evaluated 83 implants placed according to 53 sinus membrane‐elevation procedures and reported a survival rate of 94.3% after a mean follow‐up time of 4.6 years. Ellegard et al.…”
Section: Lateral Sinus Floor Elevationmentioning
confidence: 99%